Occupational asbestos exposure is associated with pharyngeal squamous cell carcinoma in men from the greater Boston area. Issue 12 (27th September 2013) - Langevin, Scott M; O'Sullivan, Mattie H; Valerio, Jennifer L; Pawlita, Michael; Applebaum, Katie M; Eliot, Melissa; McClean, Michael D; Kelsey, Karl T
Abstract : Objectives: Asbestos is the name given to a group of naturally occurring silicate mineral fibres that were widely used in industry during the 20th century due to their desirable physical properties. Although use in the USA has fallen over the last three decades, significant exposure in the developing world continues and the burden of disease is considerable. Asbestos is a known risk factor for several malignant diseases, including lung cancer and mesothelioma, and has more recently been implicated in pharyngeal and laryngeal cancer. However, studies of asbestos and cancers of the larynx or pharynx with adequate sample size that control for major head and neck squamous cell carcinoma (HNSCC) risk factors remain relatively sparse. Methods: We report findings from a case–control study of 674 incident male HNSCC cases from the greater Boston region and 857 population-based male controls, matched on age (±3 years), sex, and town or neighbourhood of residence. Multivariable logistic regression was used to assess the association between occupational asbestos exposure and HNSCC by primary tumour site. Results: 190 cases (28.2%) and 203 controls (23.7%) reported occupational exposure to asbestos. Occupational asbestos exposure was associated with elevated risk of pharyngeal carcinoma in men (OR 1.41, 95% CI 1.01 to 1.97), adjusted for age, race, smoking, alcohol consumption, education, income and HPV16 serology, with borderline increasing risk for each decade in the exposed occupation (OR 1.10, 95% CI 0.99 to 1.23). Conclusions: These observations are consistent with mounting evidence that asbestos is a risk factor for pharyngeal cancer.